Leptospiral Proteins Induced In-Vivo And Its Application In The Development Of Antibody And Antigen Detection Tests For Acute Leptospirosis - Chang, Chiat Han (2018)
Leptospirosis, caused by pathogenic Leptospira spp., is a re-emerging global health threat. Therefore, it is pertinent to identify novel diagnostic marker and investigate its potential use in antibody and antigen detection assays for detection of acute leptospirosis. Using panels of serum samples from acute (Group I) and mixed (Group II) phase leptospirosis, the present study was initiated by evaluating performance of two leptospirosis rapid diagnostic kits, namely Leptorapide and VISITECT-LEPTO, that were commonly used in Malaysia. Both test kits showed low diagnostic sensitivity (≤34%) with the acute phase serum samples, but better sensitivity with the mixed phase samples. Selected serum samples from Group I were used to identify novel diagnostic marker(s) from Leptospira genomic DNA expression library using In-vivo Induced Antigen Technology.